A Review of Dried Fruits and Vegetables Consumed In Northern Nigeria - Okaiyeto, S. A.; S. I., Ogijo; Unguwanrimi, Y. A.; Jonga, B. J.; Sada, A. M. (International Journal of Scientific Research and Management (IJSRM), 2020)
Fresh fruits and vegetables are important foods both from economic and nutritional point of view. Fruits and vegetable of all types are valuable part of our diet, however, many vegetables are highly seasonal in nature, they are available in abundance at a particular season and sometimes result in market glut, while at off-season they become very scarce and expensive. Large quantities of these vegetables are lost during or shortly after harvest due to their perishable nature.  Drying of vegetables as a means of reducing post-harvest losses and improve storability has been practiced for many centuries. As compared to fresh vegetables which can be kept for few days, dry products can be stored for months or even years without substantial loss of nutrients. This paper reviews some commonly dried fruits and vegetables consumed in northern Nigeria, which includes; Tomato, Okra, Baobab leaves, Sweet potato, Cassava, Moringa, Sorrel and Jute. A comprehensive review of preservation methods, price variation with season, storage and duration of these fruits and vegetables is presented and recommendations are made for further studies.Fresh fruits and vegetables are important foods both from economic and nutritional point of view. Fruits and vegetable of all types are valuable part of our diet, however, many vegetables are highly seasonal in nature, they are available in abundance at a particular season and sometimes result in market glut, while at off-season they become very scarce and expensive. Large quantities of these vegetables are lost during or shortly after harvest due to their perishable nature.  Drying of vegetables as a means of reducing post-harvest losses and improve storability has been practiced for many centuries. As compared to fresh vegetables which can be kept for few days, dry products can be stored for months or even years without substantial loss of nutrients. This paper reviews some commonly dried fruits and vegetables consumed in northern Nigeria, which includes; Tomato, Okra, Baobab leaves, Sweet potato, Cassava, Moringa, Sorrel and Jute. A comprehensive review of preservation methods, price variation with season, storage and duration of these fruits and vegetables is presented and recommendations are made for further studies.